Actividad empresarial y rol promotor del estado en la constitución peruana de 1993 - Gasco Valer, María del Carmen (2022)
This article proposes a constitutional approach of the role of Government in Economy, and the principle of subsidiarity in the 1993 Peruvian Constitution. The proposal discusses the generally accepted notion of promotion in Public Law, as a reference to establish when Government can develop business activity within the framework of the 1993 Constitution. The discussion adopts the point of view of the Public Law to analyze the principle of subsidiarity of Government when it comes to developing business.